Effect of Aqueous Suspensions of Titanium Dioxide in Photoreactor with Radiation Source on Color Changes of Three Contemporary Composite Resins - H.H. Alameedee, Ameer; A.M. Ragab, Hala; M.H. Osman, Essam; H. Hussein, Falah (Asian Journal of Chemistry, 2014)
The study performed to assess the effect of titanium dioxide using (Photoreactor) with the source of radiation on the color change of the three contemporary dental fillings by composite resin material. The resins were divided into three groups head of considering the type of charge and each group of which is composed of five discs and each disc thickness of 2 mm and diameter of 5 mm and manufactured by the mold of Teflon material and then been refined and soften the disc surface and stored in distilled water for one week at 37 °C in order to complete the polymerization. After the completion of the first week is staining the surface of disks and putting it in a solution of iodine mouth wash (AVALON pharma®) at 37 °C for a period of just one week after the completion of this week has been directed drive and put it in aqueous suspension consisting of titanium dioxide in Photoreactor Radiation with 355 NM periods of time 0, 5, 10, 15 and 30 seconds. Colorimetric readings were taken of the tablets based on, before staining substance iodine solution, after staining discs textured iodine solution and after treatment disks Palmalq water for titanium dioxide. In addition, the absorbance was measured after each period of time and put the disks. Palmalq watery results were analyzed statistically. There were significant effects on pay chromatography and the palace of color where are different for each group from the other and come the second group of the most influential change chromatography and minors chromatography and then finished second the third set. Finally, comes the first group, as well as influenced by absorbance time in extrusive and different for each group of the three groups of disk attributed to their chemical composition.